ACCOUNTABILITY REQUIREMENTS, AUDITING PERFORMANCE AND GENDER - Wokas, Heince R. N.; Saerang, David P.E.; Tinangon, Jantje J; Saerang, Ivonne S (Universitas Sam Ratulangi, 2020)
The purpose of this study is to identify the different types of accountability requirements and to determine whether the workload and pressure of accountability requirements affect the auditing performance of the internal auditors' Government Internal Supervisory Apparatus (or called APIP) the Regional Government Inspectorate in North Sulawesi, Indonesia both women and men, with Partial Least Squares (PLS) modeling as an analysis tool used in analyzing and interpreting the data. The results of the study using quantitative analysis showed that the auditing performance of the APIP in North Sulawesi was partly influenced by the negative perceptions of work context in the form of workload and work pressure. The auditing performance is not affected by the dimensions of accountability requirements, work pressure affects the auditing performance, and so does the gender that does not affect the auditing performance.